Profiling discourse participants : forms and functions in Spanish conversation and debates - Cock, Barbara De (Pragmatics & beyond ;, 2014)
The construction of discourse is a challenging field where many discourse structures and interactional effects remain poorly understood. This analysis provides a systematic explanation for the way in which discourse participants (speaker and hearer) are construed in Spanish through a corpus-driven analysis of informal conversation, TV-debates and parliamentary debates. It deals not only with person deixis, but with the full range of possibilities speakers choose from when profiling their self or their relationship with the interlocutor. This analysis also offers new insights into the operation.